Impact of gamification in activewear marketing on purchasing intention among Gen-Z in Malaysia - Tan, Xiao Wen; Yeak, Hui Ying (2025)
This study investigates the impact of gamification in activewear marketing on purchasing intention among Generation Z consumers in Malaysia using the Technology Acceptance Model (TAM) as the theoretical foundation. The model was extended with Perceived Social Influence (PSI) and Perceived Enjoyment (PE) to account for the social dynamics of gamified marketing. The framework includes Perceived Usefulness (PU), Perceived Ease of Use (PEoU), PE, and PSI as independent variables, Attitude (ATT) as the mediating variable, and Purchase Intention (PUI) as the dependent variable. A quantitative approach was adopted, with data collected from 384 Malaysian Gen Z respondents who had prior exposure to gamified marketing campaigns in the activewear industry. Partial Least Squares Structural Equation Modelling (PLSSEM) was used to analyze the data and evaluate the proposed relationships. The findings demonstrate that PU, PEoU, PE, and PSI significantly influence ATT, which in turn positively affects PUI. The mediating effect of ATT was also confirmed, highlighting the importance of gamification in shaping attitudes and driving purchase intentions. These results provide both theoretical contributions and practical insights for marketers and activewear brands seeking to engage Gen Z consumers more effectively. Keywords: Gamification; Perceived Usefulness (PU); Perceived Ease of Use (PEoU); Perceived Enjoyment (PE); Perceived Social Influence (PSI); Attitude (ATT); Purchase Intention (PUI); Generation Z; Activewear Marketing; Technology Acceptance Model (TAM) Subject Area: HF5410-5417.5 Marketing. Distribution of products